(untitled) (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Pregnancy is a normal and natural process in a woman where physical, psychological and social changes occur during pregnancy. Knowledge about the danger signs of pregnancy is important for the public to know, especially pregnant women because if these danger signs are known early, then treatment will be faster. This research aims is to determine the difference in the level of knowledge of pregnant women about danger signs of pregnancy before and after being given counseling at the Mejayan Community Health Center, Madiun Regency. This type of research is Quasy Experimental with a One-Group Pre-Test-Post-Test approach. The respondents used were 54 with total sampling. The instrument used is a questionnaire that has been tested for validity. Data analysis used paired t-test. The conclusion of the results p value = 0.000, which stated that there was a significant difference in the knowledge of pregnant women before and after being given health education about the dangers of pregnancy using leaflets. It is hoped that the suggestions will serve as input for pregnant women to be more active in seeking information and for health workers to be more active in providing health education and facilitating pregnant women regarding the danger signs of pregnancy. Keywords: Danger Signs of Pregnancy; Health Education; Knowledge